Late Amazonian Ice Survival in Kasei Valles, Mars. Issue 11 (24th November 2020) - Hepburn, A. J.; Ng, F. S. L.; Holt, T. O.; Hubbard, B.
Abstract: High‐obliquity excursions on Mars are hypothesized to have redistributed water from the poles to nourish mid‐latitude glaciers. Evidence of this process is provided by different types of viscous flow features (ice‐rich deposits buried beneath sediment mantle) located there today, including lobate debris aprons (LDAs). During high‐obliquity extremes, ice may have persisted even nearer the equator, as indicated by numerous enigmatic depressions bounded on one side by either isolated mesas or scarps, and on the other by a lava unit. These depressions demarcate the past interaction between flowing lava and ghost LDAs (GLDAs), which have long since disappeared. We term these features GLDA depressions, about which little is known besides their spatial extent. This collection of depressions implies tropical ice loss over an area ∼100, 000 km 2 . To constrain their history in Kasei Valles, we derive model ages for GLDA depressions, mesas, and the lava flow from crater counts. We use a 2D model of glacial ice constrained by the topography of GLDA depressions to approximate the surface and volume of former glacial ice deposits. The model reconstructs former ice surfaces along multiple flow lines orientated normal to GLDA depression boundaries. This reconstruction indicates that 1, 400–3, 500 km 3 of ice—similar to that present in Iceland on Earth—existed at ∼1.3 Ga when the lava was emplaced. Dating shows that the GLDAs survived for up to ∼1 billion years following lava emplacement, before its final demise. Plain Language Summary: Mars hosts numerous ice‐rich glacier‐like landforms throughout its mid‐latitudes. However, beyond these latitudes, in lava deposits north of the Kasei Valles channel, are a series of depressions surrounding isolated mesas and along the base of a large regional scarp. These depressions are formed as ice and lava interacted, and mark the extent of ice‐rich glaciers, at the time the lava flow was formed. Any ice involved in the formation of these glaciers has since disappeared. We conduct a regional survey of these "ghost" ice masses, and constrain their history by counting the number of impact craters on their surface, as well as those on the lava flow. We also use a 2D model of ice flow to calculate the volume of ice contained within ghost glaciers at the time the lava flow formed. We find that 1, 440–3, 450 km 3 of ice—similar to that present in Iceland on Earth—existed during the formation of the lava deposit 1.3 billion years ago. Dating of the ghost glacier depressions indicates that ice survived for up to 1 billion years following lava formation, before their final demise. Key Points: We model and date the formation of lava, and the recession of ghost lobate debris aprons (GLDAs), in Kasei Valles At the time of lava formation, 1.3 Ga, 1, 400–3, 500 km 3 of ice existed in the Kasei Valles region GLDAs survived for up to 1 Ga following the formation of lava flow